STUDY OF ORGANIC ARCHITECTURE CONCEPT IN THE RANCH MODERN AGRO-TOURISM AREA - Gina Liana Wati; Anisa Anisa (Ide dan Dialog Desain Indonesia (Idealog), 2022)
Organic architecture is a concept in architecture that is in harmony with nature. This concept can also be used to integrate several activities in a field. There are eight variables that serve as benchmarks in designing buildings with an organic architectural concept, namely, building as nature, continuous present, form follows flow, of the people, of the hill, of the material, youthful and unexpected, living music. The application of organic architecture in modern agro-tourism areas can liven up the atmosphere of modern agro-tourism areas, so as to increase the attractiveness of these modern agro-tourism areas. Agrotourism is a tourist spot that utilizes agricultural businesses such as food crops, horticulture, plantations, forestry, animal husbandry and fisheries which make great use of local natural conditions. The purpose of this study is to identify, describe and interpret the application of the concept of organic architecture in agro-tourism areas. This research is a qualitative descriptive research, which collects qualitative data through direct observation and interviews. The results obtained from this study are eight organic architectural concepts applied to agro-tourism areas, among others by making multi-mass buildings so as to create open spaces and contextual formations with the natural surroundings. This form of mass supports interaction between visitors and between visitors and animals found in agro-tourism areas. Besides that, the application of organic architecture can also be seen in the use of environmentally friendly materials and the presence of unexpected accents in the design of indoor and outdoor spaces. Keywords: organic architecture, agro-tourism, The Ranch